The existence of Indonesian local performing arts in the digital era: a quantitative content analysis of trending tik tok videos - Zandra, Rully Aprilia; Hidayatullah, Hengki Tri (Pascasarjana Institut Seni Indonesia Surakarta, 2024)
In the digital age, local Indonesian performing arts face both challenges and opportunities in terms of visibility and preservation. This research aims to analyze the characteristics of trending local Indonesian performing arts videos on the TikTok platform and to understand their demographics. The study employs a quantitative content analysis method to examine the representation and popularity of local Indonesian performing arts in trending TikTok videos. A sample of TikTok videos showcasing local dance, music, and theater from various regions of Indonesia was analyzed for themes and engagement metrics. The findings reveal that (1) Generation Z is the dominant force shaping the digital stage on TikTok, (2) performing arts creators are predominantly female, (3) local dance accompanied by a blend of traditional and modern music is a key strategy for high engagement on TikTok, (4) costumes have minimal impact on video engagement, (5) standard shooting and tilting are the most commonly used video styles, and (6) popular performing arts demographics are primarily from Java (West Java, East Java, and Yogyakarta). This research underscores the role of TikTok in revitalizing and disseminating local Indonesian performing arts while highlighting the implications for cultural preservation and audience engagement in the digital era.